PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN IPS TERPADU KELAS VIII DI MTS AL-AZHAR SAMARINDA - Ayustira, Nurwahidah; Sudarman, Sudarman; Riyadi, Riyo (Faculty of Teacher Training and Education, Mulawarman University, 2023)
This research aims to develop Android-based learning media, assess its feasibility, and evaluate student responses. The research employs the Research and Development (R&D) methodology with the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through unstructured interviews with 6 students from classes VIII B and VIII D at MTs Al-Azhar Samarinda. The research results indicate that the material expert validation test yielded 97%, media expert validation test resulted in 85%, instructional expert validation test recorded 86%, small group trial obtained 91%, and large group trial scored 95%. Overall, the Android-based learning media for Integrated Social Studies (IPS) in Grade VIII at MTs Al-Azhar Samarinda scored 91%, indicating its